High-flame-retardant high-impact-strength polycarbonate coiled material composite material and preparation method thereof

By using composite flame retardant and toughening agent in polycarbonate materials, the problem of insufficient flame retardant and impact strength of polycarbonate materials is solved, and a high flame retardant and high impact strength polycarbonate coil composite material is prepared, achieving functional improvement and process simplification.

CN119899505APending Publication Date: 2025-04-29HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311405562.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The flame retardancy and impact strength of existing polycarbonate materials are insufficient, making it difficult to meet the high requirements of materials in the new energy industry.

Method used

By innovatively combining a mixture of perfluorobutylsulfonate and phosphazene flame retardant (flame retardant A) with polymethylsiloxane or polydimethylsiloxane flame retardant (flame retardant B), combined with methyl methacrylate-stendin-styrene core-shell polymer as toughening agent, the polycarbonate material is modified to prepare a high flame retardant and high impact strength polycarbonate coil composite material with high flame retardant and high impact strength.

Benefits of technology

The high flame retardancy and high impact strength of polycarbonate coil composite materials are achieved, giving traditional materials better functionality, and at the same time, the preparation process is simple and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004516462320000121
    Figure BDA0004516462320000121
Patent Text Reader

Abstract

The invention discloses a high-flame-retardant high-impact-strength polycarbonate coiled material composite material and a preparation method thereof, and belongs to the field of polycarbonate coiled material modification, the composite material comprises the following components by weight: 100 parts of polycarbonate resin, 0.2-1 part of a flame retardant A, 0.2-1 part of a flame retardant B, 1-5 parts of a flexibilizer, 0.05-0.5 part of an antioxidant, and 0.05-0.5 part of a lubricant; the flame retardant A is a mixture of perfluorobutyl sulfonate and a phosphazene flame retardant; and the flame retardant B is a polymethylsiloxane or polydimethylsiloxane flame retardant. The polycarbonate coiled material composite material prepared by the invention has the characteristics of high flame retardance, high impact and the like, and a traditional plastic coiled material is endowed with certain functionality. In addition, equipment and a process required for preparing the composite material are simple, and direct large-scale production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polycarbonate coil modification, and particularly relates to a high flame retardant and high impact strength polycarbonate coil composite material and a preparation method thereof. Background Art

[0002] Polycarbonate is a common engineering plastic modified matrix resin with high strength and good dielectric properties. It is widely used in electronic appliances, transportation and other fields. In recent years, with the rapid development of the new energy industry, polycarbonate can be used as cover plates and gaskets in related fields after being formed into coils using sheet extrusion production lines. However, with the emergence of new applications, some requirements such as flame retardancy and strength have been put forward for such materials, which are difficult to meet with traditional materials. Summary of the invention

[0003] The purpose of the present invention is to provide a highly flame-retardant and high-impact-strength polycarbonate coil composite material and a preparation method thereof, so as to solve the problems of low flame retardancy and low impact strength of polycarbonate materials in the prior art. The present invention innovatively utilizes flame retardants and toughening agents to modify polycarbonate materials and applies them to the coil field to prepare a highly flame-retardant and high-impact-strength polycarbonate coil composite material, which gives the composite material high flame retardancy and high impact strength characteristics on the basis of traditional materials. In addition, the equipment and process required for the preparation of the composite material involved in the present invention are simple, and can be directly mass-produced.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] A highly flame-retardant and high-impact polycarbonate coil composite material comprising the following components and their weight contents:

[0006] 100 parts of polycarbonate resin,

[0007] Flame retardant A 0.2-1 part,

[0008] Flame retardant B 0.2~1 part,

[0009] 1 to 5 parts of toughening agent,

[0010] 0.05-0.5 parts of antioxidant,

[0011] Lubricant 0.05-0.5 parts;

[0012] in:

[0013] Flame retardant A is a mixture of perfluorobutyl sulfonate and phosphazene flame retardant; preferably, the phosphazene flame retardant is polydiphenylphosphazene or hexaphenoxy cyclotriphosphazene; the mass ratio of perfluorobutyl sulfonate to phosphazene flame retardant in flame retardant A is (2-3): (7-8).

[0014] The flame retardant B is polymethylsiloxane or polydimethylsiloxane flame retardant.

[0015] The melt index of polycarbonate resin is 10-20g / 10min at a temperature of 300°C and a load of 1.2Kg.

[0016] The toughening agent is methyl methacrylate-butadiene-styrene core-shell polymer.

[0017] The antioxidant is at least one of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and bis(2,4-diacyl)pentaerythritol diphosphite.

[0018] The lubricant is pentaerythritol stearate or ethylene-acrylic acid copolymer wax.

[0019] The present invention also provides a method for preparing the above-mentioned high flame retardant and high impact strength polycarbonate coil composite material, comprising the following steps:

[0020] (1) After weighing the raw materials of each component according to the proportion, the raw materials are placed in a high-speed mixer and stirred and dispersed for 10 to 30 minutes to obtain a mixed material;

[0021] (2) The mixed material is passed through an extruder, melted, plasticized, and extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0022] The high flame retardant and high impact polycarbonate coil composite material prepared by the invention has the characteristics of high flame retardancy and high impact, and endows the traditional plastic coil with certain functionality.

[0023] The specific beneficial effects are as follows:

[0024] 1. Compared with the flame retardant used alone, the compound flame retardant can play a synergistic role in the flame retardant mechanism. The present invention innovatively uses flame retardant A containing perfluorobutyl sulfonate and phosphazene flame retardant and flame retardant B (polymethylsiloxane or polydimethylsiloxane) to compound flame retardants. When the coil burns, the phosphazene flame retardant is thermally decomposed to generate phosphoric acid, metaphosphoric acid and polyphosphoric acid, which can form a protective film on the surface of the material to isolate the air, and further decompose water and carbon dioxide to further inhibit the combustion. Perfluorobutyl sulfonate flame retardant can accelerate the cross-linking rate between polycarbonate molecular segments, and polymethylsiloxane or polydimethylsiloxane flame retardant can form a carbon blocking layer, which synergizes with each other to achieve excellent flame retardant effect;

[0025] 2. This patent uses methyl methacrylate-butadiene-styrene core-shell polymer as a toughening agent, which can effectively reduce the stress concentration effect and slow down the generation and development of silver streaks when the composite material is punctured or impacted by external forces. In addition, the polymethylsiloxane and polydimethylsiloxane flame retardants contained in the formula can change the direction of the development of silver streaks when the material is damaged, playing a synergistic toughening role.

[0026] Therefore, the polycarbonate coil composite material prepared by the present invention has the characteristics of high flame retardancy and high impact, and gives the traditional plastic coil a certain functionality. In addition, the equipment and process required for the preparation of the composite material involved in the present invention are simple and can be directly mass-produced. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0028] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional means in the prior art in the art, and therefore, they are not described in detail; the parts in the following embodiments are all parts by weight.

[0029] The specific embodiments of the present invention are as follows:

[0030] Example 1

[0031] (1) Prepare the raw materials in the following proportions:

[0032] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0033] 0.2 parts of flame retardant A with a mass ratio of perfluorobutyl sulfonate to polydiphenylphosphazene of 3:7,

[0034] 0.2 parts of polymethylsiloxane flame retardant,

[0035] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0036] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0037] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.03 parts,

[0038] Lubricant: pentaerythritol stearate 0.05 parts.

[0039] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0040] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0041] Example 2

[0042] (1) Prepare the raw materials in the following proportions:

[0043] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0044] 0.4 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate to polydiphenylphosphazene of 3:7,

[0045] 0.4 parts of polymethylsiloxane flame retardant,

[0046] 2 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0047] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.05 parts,

[0048] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.1 parts,

[0049] Lubricant: 0.15 parts of pentaerythritol stearate.

[0050] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 15 minutes;

[0051] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0052] Example 3

[0053] (1) Prepare the raw materials in the following proportions:

[0054] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0055] 0.6 parts of flame retardant A with a mass ratio of perfluorobutyl sulfonate to polydiphenylphosphazene of 3:7,

[0056] 0.6 parts of polymethylsiloxane flame retardant,

[0057] 3 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0058] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.1 parts,

[0059] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.15 parts,

[0060] Lubricant: 0.25 parts of pentaerythritol stearate.

[0061] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 20 minutes;

[0062] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0063] Example 4

[0064] (1) Prepare the raw materials in the following proportions:

[0065] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0066] 0.8 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate to polydiphenylphosphazene of 3:7,

[0067] 0.8 parts of polymethylsiloxane flame retardant,

[0068] 4 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0069] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.15 parts,

[0070] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.2 parts,

[0071] Lubricant: 0.35 parts of pentaerythritol stearate.

[0072] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 25 minutes;

[0073] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0074] Example 5

[0075] (1) Prepare the raw materials in the following proportions:

[0076] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0077] 1 part of flame retardant A with a mass ratio of perfluorobutane sulfonate to polydiphenylphosphazene of 3:7,

[0078] 1 part of polymethylsiloxane flame retardant,

[0079] 5 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughening agent,

[0080] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.2 parts,

[0081] 0.3 parts of antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate,

[0082] Lubricant: 0.5 parts of pentaerythritol stearate.

[0083] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 30 minutes;

[0084] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0085] Example 6

[0086] (1) Prepare the raw materials in the following proportions:

[0087] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0088] 0.8 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0089] 0.8 parts of polydimethylsiloxane flame retardant,

[0090] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0091] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0092] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0093] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0094] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0095] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0096] Example 7

[0097] (1) Prepare the raw materials in the following proportions:

[0098] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0099] 0.4 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0100] 0.4 parts of polydimethylsiloxane flame retardant,

[0101] 2 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0102] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.05 parts,

[0103] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.1 part,

[0104] Lubricant ethylene-acrylic acid copolymer wax 0.15 parts.

[0105] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 15 minutes;

[0106] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0107] Example 8

[0108] (1) Prepare the raw materials in the following proportions:

[0109] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0110] 0.6 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0111] 0.6 parts of polydimethylsiloxane flame retardant,

[0112] 3 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0113] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.1 parts,

[0114] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.15 parts,

[0115] Lubricant ethylene-acrylic acid copolymer wax 0.25 parts.

[0116] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 20 minutes;

[0117] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0118] Example 9

[0119] (1) Prepare the raw materials in the following proportions:

[0120] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0121] 0.2 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0122] 0.2 parts of polydimethylsiloxane flame retardant,

[0123] 4 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0124] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.15 parts,

[0125] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.2 parts,

[0126] Lubricant ethylene-acrylic acid copolymer wax 0.35 parts.

[0127] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 25 minutes;

[0128] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0129] Example 10

[0130] (1) Prepare the raw materials in the following proportions:

[0131] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0132] 1 part of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0133] 1 part of polydimethylsiloxane flame retardant,

[0134] 5 parts of methyl methacrylate-butadiene-styrene core-shell polymer toughening agent,

[0135] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.2 parts,

[0136] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.3 parts,

[0137] Lubricant ethylene-acrylic acid copolymer wax 0.5 parts.

[0138] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 30 minutes;

[0139] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0140] Comparative Example 1

[0141] (1) Prepare the raw materials in the following proportions:

[0142] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0143] 0.2 parts of perfluorobutyl sulfonate flame retardant,

[0144] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0145] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.1 parts,

[0146] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.15 parts,

[0147] Lubricant: 0.25 parts of pentaerythritol stearate.

[0148] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 20 minutes;

[0149] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0150] Comparative Example 2

[0151] (1) Prepare the raw materials in the following proportions:

[0152] 100 parts of polycarbonate resin with a melt index of 10 g / 10 min (300°C / 1.2 kg),

[0153] 0.4 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate to polydiphenylphosphazene of 3:7,

[0154] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0155] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0156] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0157] Lubricant: pentaerythritol stearate 0.05 parts.

[0158] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0159] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0160] Comparative Example 3

[0161] (1) Prepare the raw materials in the following proportions:

[0162] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0163] 0.2 parts of polymethylsiloxane flame retardant,

[0164] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0165] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0166] Antioxidant β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 0.03 parts,

[0167] Lubricant: pentaerythritol stearate 0.05 parts.

[0168] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0169] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0170] Comparative Example 4

[0171] (1) Prepare the raw materials in the following proportions:

[0172] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0173] 0.2 parts of flame retardant A with a mass ratio of perfluorobutyl sulfonate to polydiphenylphosphazene of 3:7,

[0174] Sodium benzenesulfonate flame retardant 0.2 parts,

[0175] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0176] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0177] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0178] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0179] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0180] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0181] Comparative Example 5

[0182] (1) Prepare the raw materials in the following proportions:

[0183] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0184] 0.2 parts of polymethylsiloxane flame retardant,

[0185] Sodium benzenesulfonate flame retardant 0.2 parts,

[0186] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0187] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0188] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0189] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0190] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0191] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0192] Comparative Example 6

[0193] (1) Prepare the raw materials in the following proportions:

[0194] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0195] 1.6 parts of flame retardant A with a mass ratio of perfluorobutane sulfonate and hexaphenoxy cyclotriphosphazene of 2:8

[0196] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0197] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0198] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0199] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0200] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0201] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0202] Comparative Example 7

[0203] (1) Prepare the raw materials in the following proportions:

[0204] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0205] 1.6 parts of polydimethylsiloxane flame retardant,

[0206] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0207] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0208] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0209] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0210] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0211] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0212] Comparative Example 8

[0213] (1) Prepare the raw materials in the following proportions:

[0214] 100 parts of polycarbonate resin with a melt index of 20 g / 10 min (300°C / 1.2 kg),

[0215] 1.6 parts of perfluorobutyl sulfonate

[0216] 0.2 parts of polydimethylsiloxane flame retardant,

[0217] 1 part of methyl methacrylate-butadiene-styrene core-shell polymer toughener,

[0218] Antioxidant N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine 0.02 parts,

[0219] Antioxidant bis(2,4-diacid)pentaerythritol diphosphite 0.03 parts,

[0220] Lubricant ethylene-acrylic acid copolymer wax 0.05 parts.

[0221] (2) Place the above raw materials together in a high-speed mixer and stir and disperse for 10 minutes;

[0222] (3) The dispersed raw materials are passed through an extruder (extrusion temperature: zone 1: 240° C., zone 2: 245° C., zone 3: 250° C., zone 4: 260° C., zone 5: 260° C., zone 6: 260° C., zone 7: 260° C., main engine speed: 400 rpm), melted, plasticized, extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

[0223] The materials prepared in the above examples and control examples were subjected to performance tests. After the prepared samples were conditioned at 23°C and 50% humidity, the flame retardancy and impact strength of the composite coils were tested using UL94 and GB9639 standards, respectively. The test results are shown in Table 1:

[0224]

[0225] The polycarbonate coil composite material prepared by the present invention has the characteristics of high flame retardancy and high impact, and gives the traditional plastic coil a certain functionality. As can be seen from the data in Table 1, the high flame retardant and high impact polycarbonate coil composite material prepared by the present invention using high viscosity polycarbonate with a melt index of 10g / 10min has a flame retardancy of V-0 (Example 3 and Example 4) at a thickness of 0.5mm, HB for the control example 1, and V-2 for the control example 2; the flame retardancy of the material prepared by Example 5 is V-1, and it can be seen that when the amount of flame retardant is too much, the flame retardant will not be well dispersed due to the agglomeration phenomenon, and the flame retardant effect will become worse, so the amount of flame retardant is not better; the impact strength of the prepared material is 5800g (Example 3), which is 75.76% higher than that of the control example 1 and 87.10% higher than that of the control example 2. The present invention uses a high flame retardant and high impact polycarbonate coil composite material prepared by a low viscosity polycarbonate with a melt index of 20g / 10min. The flame retardancy of 0.5mm thickness is optimally V-0 (Example 6), while the control example 4 is V-2 and the control example 5 is V-2; the maximum impact strength is 5400g (Example 9), which is 54.29% higher than the control example 4 and 63.64% higher than the control example 5; by comparing Example 6 with the control examples 6 to 8, it can be seen that the flame retardant A and the flame retardant B can produce a synergistic effect to improve the flame retardant properties of the material; and polydimethylsiloxane can play a synergistic toughening role with the methyl methacrylate-butadiene-styrene core-shell polymer to improve the impact strength of the material. In addition, the equipment and process required for the preparation of the composite material involved in the present invention are simple and can be directly mass-produced.

[0226] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these examples and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A highly flame-retardant and high-impact polycarbonate coil composite material, characterized in that: Contains the following components and weight content: 100 parts of polycarbonate resin, Flame retardant A 0.2-1 part, Flame retardant B 0.2~1 part, 1 to 5 parts of toughening agent, 0.05-0.5 parts of antioxidant, Lubricant 0.05-0.5 parts; The flame retardant A is a mixture of perfluorobutyl sulfonate and phosphazene flame retardant; The flame retardant B is polymethylsiloxane or polydimethylsiloxane flame retardant.

2. The highly flame-retardant and high-impact polycarbonate coil composite material according to claim 1, characterized in that: The phosphazene flame retardant is polydiphenylphosphazene or hexaphenoxy cyclotriphosphazene.

3. The highly flame-retardant and high-impact polycarbonate coil composite material according to claim 1, characterized in that: The mass ratio of perfluorobutyl sulfonate to phosphazene flame retardant in the flame retardant A is (2-3): (7-8).

4. The highly flame-retardant and high-impact polycarbonate coil composite material according to claim 1, characterized in that: The polycarbonate resin has a melt index of 10-20 g / 10 min at a temperature of 300° C. and a load of 1.2 kg.

5. The highly flame-retardant and high-impact polycarbonate coil composite material according to claim 1, characterized in that: The toughening agent is methyl methacrylate-butadiene-styrene core-shell polymer.

6. The highly flame-retardant and high-impact polycarbonate coil composite material according to claim 1, characterized in that: The antioxidant is at least one of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and bis(2,4-diacid)pentaerythritol diphosphite.

7. The highly flame-retardant and high-impact-strength polycarbonate coil composite material according to claim 1, characterized in that: The lubricant is pentaerythritol stearate or ethylene-acrylic acid copolymer wax.

8. The method for preparing the highly flame-retardant and high-impact-strength polycarbonate coil composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weighing the raw materials of each component according to the proportion and mixing them evenly to obtain a mixed material; (2) The mixed material is passed through an extruder, melted, plasticized, and extruded, and then passed through a sheet extrusion production line to obtain a highly flame-retardant and high-impact polycarbonate coil composite material.

Citation Information

Patent Citations

  • Power converter utilizing line replaceable units.

    GB2240225A